Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages 7 Still less do the scholarships awarded by universities go to the poor. Most of these are given without reference to parents' means ; indeed, between two candidates of equal ability, there may be a preference for the public school type. In December, 1942, 80 per cent. of those who won scholarships to Oxford and 60 per cent. of those who won them to Cambridge came from the Public Schools. These figures are the more striking when it is remembered what a small number come from the "Public" schools, as compared with the vast public secondary school population — about 80 per cent. of all those receiving secondary education. The number of scholarships per thousand of the respective school population illustrates this : Table showing the incidence of scholarships and exhibitions to Oxford and Cambridge 1933-34. Type of School No. of Scholarships Won. Percentage of Scholarships won. Number of Scholarships per 1,000 Open Scholarships. Public and Private 287 52.7% 4.08 Grant-earning Secondary 258 47.3% 1.25 Closed Scholarships. Public and Private 241 82.8% 3.86 Grant-earning Secondary 50 17.2% 0.24 (3) Waste of Ability. It is unhappily true that ability is somewhat lower among the poorest classes. Bad food, lack of sleep have their effect on mental as on physical health. The results of intelligence tests on 13,000 Northumberland school-children were classified according to the occupations of fathers:— Occupation of Fathers. Average I.Q. of children.* Professional 112.2 Managerial 110.0 Higher Commercial 109.3 Armv, Navy, Police, Postmen 105.5 Shop-keeping 105.0 Engineering 102.9 Foremen 102.7 Building 102.0 Metal Workers, Ship-builders 100.9 Miscellaneous Industrial Workers 100.6 Miners and Quarrymen 97.6 Agriculture (all classes) 97.6 Low Grade Occupations 96.0 The handicap in ability could be overcome in one generation by proper conditions. But even granted the lower level, the ability which survives is wasted to an appalling degree. Only 11 or 12 per cent. of elementary school-children go on to secondary * Social Structure of England and Wales, p. 207. 15X/2/98/13